Historical view on the attempts to understand the function of sleep in the school of Ivan Pavlov and his Russian forerunners and followers. Issue 1 (11th March 2019) - Pigarev, Ivan N; Pigareva, Marina L
We reviewed the ideas of Ivan Pavlov and his Russian forerunners (Ivan Tarkhanov and Maria Manaseina) and followers (Nikolai Rozjanskiy and Konstantin Bykov) on the functional role of sleep. This analysis led to the conclusion that the state of sleep is connected with functional operations that have not been considered in the past and are also not being investigated in present neuroscience. Thus, a real understanding of the function of sleep may only come with a new neurophysiological paradigm.